2014
DOI: 10.1186/s12939-014-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in mental well-being among Hungarian adolescents: a cross-sectional study

Abstract: IntroductionAccording to several empirical studies, mental well-being is significant in adolescence; adolescent’s social network is undergoing radical changes while at the same time depression is increasing. The primary goal of our study is to determine whether socioeconomic status (SES) is associated with mental health status of Hungarian adolescents and the strength and nature of this association.MethodsOur sample was comprised of three high schools of Debrecen (the second largest city of Hungary). Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 56 publications
3
36
0
1
Order By: Relevance
“…The risky families model suggests that childhood adversity influences psychological distress in adulthood through resultant social impairments and deficits in emotion regulation (Repetti et al, 2002), such as poor social skills, impulsivity (Sheikh, 2017b), reactive aggression, behavioural problems, excessive reassurance-seeking, constricted emotions, attenuated empathy, contextually inappropriate displays of affection, and externalising behaviours, all of which are associated with peer rejection (Ban & Oh, 2016;Barnes et al, 2016). Chronic stress (i.e., the cumulative load of day-to-day stresses) in childhood caused by socioeconomic and psychosocial adversity (Sheikh, 2017b) may foster social and behavioural impairments such as low self-esteem (Mossakowski, 2015;Varga, Piko, & Fitzpatrick, 2014), cynicism regarding others' intentions and behaviours, uncontrolled behaviours in social interactions, and mistrust, all of which affect may the quality and quantity of social relationships over the life course (Coleman, Zawadzki, Heron, Vartanian, & Smyth, 2016;Etherington et al, 2016;Goodwin-Smith et al, 2017). In contrast, individuals with good emotion regulation have the ability to respond to ongoing demands with a range of socially acceptable responses such as cooperation and conciliation (Kim & Cicchetti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The risky families model suggests that childhood adversity influences psychological distress in adulthood through resultant social impairments and deficits in emotion regulation (Repetti et al, 2002), such as poor social skills, impulsivity (Sheikh, 2017b), reactive aggression, behavioural problems, excessive reassurance-seeking, constricted emotions, attenuated empathy, contextually inappropriate displays of affection, and externalising behaviours, all of which are associated with peer rejection (Ban & Oh, 2016;Barnes et al, 2016). Chronic stress (i.e., the cumulative load of day-to-day stresses) in childhood caused by socioeconomic and psychosocial adversity (Sheikh, 2017b) may foster social and behavioural impairments such as low self-esteem (Mossakowski, 2015;Varga, Piko, & Fitzpatrick, 2014), cynicism regarding others' intentions and behaviours, uncontrolled behaviours in social interactions, and mistrust, all of which affect may the quality and quantity of social relationships over the life course (Coleman, Zawadzki, Heron, Vartanian, & Smyth, 2016;Etherington et al, 2016;Goodwin-Smith et al, 2017). In contrast, individuals with good emotion regulation have the ability to respond to ongoing demands with a range of socially acceptable responses such as cooperation and conciliation (Kim & Cicchetti, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Well-established research says that a family's negative socioeconomic living circumstances have implications on youth well-being (8-10, 12, 17, 18). Focusing specifically on parental unemployment, research has demonstrated that children of unemployed parents have a higher 4 prevalence of depression symptoms, higher rates of psychosomatic symptoms and lower perceptions of psychological well-being (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Raffaelli, Koller, Cerqueira‐Santos, and De Morais (), for example, showed that low parental education, unemployment and single‐parent families are predictors of poor mental health outcomes in children and adolescents. Family income has also been associated with children's and adolescents' mental health (Dearing, McCartney, & Taylor, ; Reiss, ; Varga, Piko, & Fitzpatrick, ). Bask () and Ma, Han, Grogan‐Kaylor, Delva, and Castillo () found that low family income is a significant predictor of adolescent behavioural problems, especially internalising behaviours.…”
mentioning
confidence: 99%